2022
DOI: 10.1177/21925682211070823
|View full text |Cite
|
Sign up to set email alerts
|

Household Income as a Predictor for Surgical Outcomes and Opioid Use After Spine Surgery in the United States

Abstract: Study Design Cross-Sectional Study Objectives Socioeconomic status (SES) is a fundamental root of health disparities, however, its effect on surgical outcomes is often difficult to capture in clinical research, especially in spine surgery. Here, we present a large single-center study assessing whether SES is associated with cause-specific surgical outcomes. Methods Patients undergoing spine surgery between 2015 and 2019 were assigned income in accordance with the national distribution and divided into quartile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Low-income is also associated with longer postoperative lengths of stay, increased emergency department visits, and decreased accessibility to spinal imaging. 6,7 Medical literature has reported similar findings when examining other social determinants of health, including race, [8][9][10] ethnicity, 11,12 insurance status, 13 work status, 14,15 and education. 16 These studies highlight the importance of understanding a patient's socioeconomic profile to optimize their treatment and outcomes following spine surgery.…”
mentioning
confidence: 65%
“…Low-income is also associated with longer postoperative lengths of stay, increased emergency department visits, and decreased accessibility to spinal imaging. 6,7 Medical literature has reported similar findings when examining other social determinants of health, including race, [8][9][10] ethnicity, 11,12 insurance status, 13 work status, 14,15 and education. 16 These studies highlight the importance of understanding a patient's socioeconomic profile to optimize their treatment and outcomes following spine surgery.…”
mentioning
confidence: 65%
“…We intend our study to be foundational for development of granular models derived from multiple data sources. Moreover, variables such as socioeconomic status, education, and income level have shown potential in improving predictive accuracy 40. Measuring social support through the Risk Assessment and Prediction Tool (RAPT) presents a valuable future avenue 41.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, variables such as socioeconomic status, education, and income level have shown potential in improving predictive accuracy. 40 Measuring social support through the Risk Assessment and Prediction Tool (RAPT) presents a valuable future avenue. 41 Lastly, while this retrospective study utilized ICD10 codes to acquire components of patient data, some uncertainty on accuracy of ICD10 codes has been reported that could have resulted in an underestimation of risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have linked components of SES to poor outcomes following spine surgery 5–7. The Area of Deprivation Index (ADI), a metric similar to DCI, found an association between SES and length of stay 13,14.…”
Section: Discussionmentioning
confidence: 99%
“…While health outcome disparities among patients of lower socioeconomic standing are likely multifactorial, limited access to care or a general fear of physicians may contribute 4. In spine surgery, extensive research has been performed on how individual factors contribute to SES including insurance status, income, race and education 5–8. However, each of these aspects are difficult to investigate in isolation as they are strongly correlated with each other.…”
mentioning
confidence: 99%